2016
DOI: 10.1538/expanim.15-0057
|View full text |Cite
|
Sign up to set email alerts
|

Production of human apolipoprotein(a) transgenic NIBS miniature pigs by somatic cell nuclear transfer

Abstract: Most cases of ischemic heart disease and stroke occur as a result of atherosclerosis. The purpose of this study was to produce a new Nippon Institute for Biological Science (NIBS) miniature pig model by somatic cell nuclear transfer (SCNT) for studying atherosclerosis. The human apolipoprotein(a) (apo(a)) genes were transfected into kidney epithelial cells derived from a male and a female piglet. Male cells were used as donors initially, and 275 embryos were transferred to surrogates. Three offspring were deli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…On the basis of their anatomical and physiological similarities to humans, their high fertility and easy maintenance, the possibility of dietary and surgical interventions and the efficient and specific genetic modifications, pigs are promising models to overcome gaps between proof-of-concept models and clinical studies in obesity and diabetes mellitus research. In addition, pigs might serve as tissue donors for β-cell replacement therapies of Understanding the roles of ApoC-III in lipid metabolism and of triglycerides in atherosclerosis; evaluating drugs for hypertriglyceridemia 391 Expression of human ApoA 392,393 High plasma levels of human ApoA 393 Evaluating the pharmacology and efficacy of new drugs for atherosclerosis 393 Knockout of the gene encoding LDL receptor 394,395 Moderate (LDLR +/-) or severe (LDLR -/-) increase in total and LDL cholesterol on a standard diet; more severe on a high-fat, high-cholesterol diet 21 ; atherosclerotic lesions in the coronary arteries and abdominal aorta (LDLR -/-) 394,395 Developing and testing novel detection and treatment strategies for coronary and aortic atherosclerosis and its complications [394][395][396] Overexpression of LDL-PLA(2) 397 Increased postprandial plasma triglyceride levels; increased expression of pro-inflammatory genes in peripheral blood mononuclear cells 397 Studying the consequences of elevated circulating LDL-PLA(2) levels; testing LDL-PLA(2) inhibitors 397 ApoA, apolipoprotein(a); ApoC-III, apolipoprotein C-III; GIPR, glucose-dependent insulinotropic polypeptide receptor; HNF1A, hepatocyte nuclear factor 1α; LDL-PLA(2), LDL-associated phospholipase A2; PCSK9, proprotein convertase subtilisin/kexin type 9. *The pathological changes in this model may be caused by expression of mutant HNF1A and not be a consequence of diabetes mellitus.…”
Section: Large Animal Modelsmentioning
confidence: 99%
“…On the basis of their anatomical and physiological similarities to humans, their high fertility and easy maintenance, the possibility of dietary and surgical interventions and the efficient and specific genetic modifications, pigs are promising models to overcome gaps between proof-of-concept models and clinical studies in obesity and diabetes mellitus research. In addition, pigs might serve as tissue donors for β-cell replacement therapies of Understanding the roles of ApoC-III in lipid metabolism and of triglycerides in atherosclerosis; evaluating drugs for hypertriglyceridemia 391 Expression of human ApoA 392,393 High plasma levels of human ApoA 393 Evaluating the pharmacology and efficacy of new drugs for atherosclerosis 393 Knockout of the gene encoding LDL receptor 394,395 Moderate (LDLR +/-) or severe (LDLR -/-) increase in total and LDL cholesterol on a standard diet; more severe on a high-fat, high-cholesterol diet 21 ; atherosclerotic lesions in the coronary arteries and abdominal aorta (LDLR -/-) 394,395 Developing and testing novel detection and treatment strategies for coronary and aortic atherosclerosis and its complications [394][395][396] Overexpression of LDL-PLA(2) 397 Increased postprandial plasma triglyceride levels; increased expression of pro-inflammatory genes in peripheral blood mononuclear cells 397 Studying the consequences of elevated circulating LDL-PLA(2) levels; testing LDL-PLA(2) inhibitors 397 ApoA, apolipoprotein(a); ApoC-III, apolipoprotein C-III; GIPR, glucose-dependent insulinotropic polypeptide receptor; HNF1A, hepatocyte nuclear factor 1α; LDL-PLA(2), LDL-associated phospholipase A2; PCSK9, proprotein convertase subtilisin/kexin type 9. *The pathological changes in this model may be caused by expression of mutant HNF1A and not be a consequence of diabetes mellitus.…”
Section: Large Animal Modelsmentioning
confidence: 99%
“…Increased plasma concentrations of lipoprotein (a) are linked to an increased risk for coronary heart disease (Saleheen et al 2017). Transgenic pigs (two different minipig strains) expressing human Apo (a) under the control of an ubiquitously active promoter (Ozawa et al 2015;Shimatsu et al 2016) revealed increased plasma concentrations of lipoprotein (a) while total cholesterol, triglyceride, LDL and HDL concentrations were unaltered compared to non-transgenic controls. The effects of human Apo (a) expression on the susceptibility to atherosclerosis in these pigs has not yet been evaluated.…”
Section: Overexpression Of Apolipoproteinsmentioning
confidence: 99%